How Could Deportation become Illegal Deportation? (The Case of Deportation of Myanmar Nationals by Malaysia) - Ikaningtyas; Susanto, Fransiska A.; Majid, Yasniar Rachmawati; Nursasmita, M. Akbar (Padjadjaran Journal of International Law, 2023)
February 2022; Malaysia deported more than 1000 undocumented migrants from Myanmar back to Myanmar, even though a coup d’état had already occurred in Myanmar. This paper will explore the nexus between coup d’état and well-founded fear of persecution and assess the decision by Malaysia to deport Myanmar immigrants back to Myanmar with the nonrefoulement principle. This paper's findings showed a clear nexus between a coup d’état and well-founded fear of persecution to some extent; the nexus appears when the Coup creates uncertainty in citizen's live and people in a dangerous situation. Consequently, the deportation decision by Malaysia violated the non-refoulment principle, and the deportation became illegal. This paper utilized the normative method to analyze the research problem.